2017
DOI: 10.5751/es-09144-220225
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between payments for hydrologic services, landowner decisions, and ecohydrological consequences: synergies and disconnection in the cloud forest zone of central Veracruz, Mexico

Abstract: . 2017. Interactions between payments for hydrologic services, landowner decisions, and ecohydrological consequences: synergies and disconnection in the cloud forest zone of central Veracruz, Mexico. ABSTRACT. Payments for Hydrologic Services (PHS) programs are increasingly used as a policy tool to provide incentives for upstream landowners to adopt land use activities that favor sustainable provision of high-quality water to downstream areas. However, the effectiveness of PHS programs in achieving their objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 89 publications
(150 reference statements)
2
21
0
2
Order By: Relevance
“…Despite remarkable progress in long‐term observations and data acquisition in Latin America (e.g., Asbjornsen et al, ; Asbjornsen et al, ; Bruijnzeel, Mulligan, & Scatena, ; Gotsch et al, ; Moore, Orozco, Aparecido, & Miller, in press; Ogden & Stallard, ), the establishment and augmentation of long‐term data networks remains logistically challenging, particularly at the highest elevations. This challenge results in an ever‐growing scientific gap that hinders our understanding of differences and similarities between hydrological processes in tropical (e.g., tropical Latin America) and temperate (e.g., North America and Europe) regions (e.g., Boulton et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite remarkable progress in long‐term observations and data acquisition in Latin America (e.g., Asbjornsen et al, ; Asbjornsen et al, ; Bruijnzeel, Mulligan, & Scatena, ; Gotsch et al, ; Moore, Orozco, Aparecido, & Miller, in press; Ogden & Stallard, ), the establishment and augmentation of long‐term data networks remains logistically challenging, particularly at the highest elevations. This challenge results in an ever‐growing scientific gap that hinders our understanding of differences and similarities between hydrological processes in tropical (e.g., tropical Latin America) and temperate (e.g., North America and Europe) regions (e.g., Boulton et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Temporal scales also matter in assessing hydrologic responses to land cover change. A study in the highlands of Veracruz, Mexico, showed that conversion of cloud forest to pasture led to increases in peak flows and decreases in dry-season flow, while reforestation with pines could either increase or decrease water yield depending largely on stand age and the timing of specific management practices (Asbjornsen et al 2017).…”
Section: Scale Effectsmentioning
confidence: 99%
“…Although, this program aims to reduce soil erosion and improve water quality and supply, such HS are not directly monitored [ 28 , 31 ]. Instead, relying on the largely untested assumption of avoided deforestation serving as a proxy for the enhancement of HS [ 31 33 ]. As Wunder et al [ 34 ] notes, for any payment to be conditional it must be possible to verify the existing service provisioning.…”
Section: Introductionmentioning
confidence: 99%
“…More quantitative evaluations of how PHS programs succeed or fail in achieving their objectives are urgently needed [ 35 ]. Relatively, few programs have been subject to evaluations of their effectiveness and impacts [ 23 , 27 , 32 33 ]. Research has tended to focus narrowly on quantifying the impact of PHS in reducing poverty or deforestation rather than ensuring provision of HS to downstream users [ 51 52 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation